Acid dulls the senses: impaired locomotion and foraging performance in a marine mollusc. (August 2015) - Leung, Jonathan Y.S.; Russell, Bayden D.; Connell, Sean D.; Ng, Jenny C.Y.; Lo, Mavis M.Y.
Abstract : The possible impacts of ocean acidification have gained substantial attention for their potential to alter physiological functioning of marine organisms. Less recognized are the present impacts of estuarine acidification, a widespread form of coastal acidification caused by terrestrial runoff and coastal current dynamics. We examined the effects of acidification (pH 8.0, 7.5 and 7.0) on the locomotory activity, respiration rate and foraging performance of a scavenging gastropod, Nassarius festivus, which relies on chemoreception to locate food sources. In addition, we assessed its ability to recover from exposure to acidified conditions, following 48 h at pH 8.0. The lowest pH conditions drove a greater proportion of individuals to retract into their shell, reduced respiration rate and resulted in worse foraging performance (i.e. lower travel speed during foraging, foraging success and consumption rate and longer feeding time). Nevertheless, individuals could recover from the effects of short-term acidification when the pH returned to normal. Overall, we demonstrated that foraging performance can be compromised by acidification, for which a global reduction in pH is set to force greater amplitudes of pH fluctuation, causing longer periods of acidification, shorter periods of recovery and potentially changing ecological roles such as nutrient recycling in coastal waters. Highlights: The effect of reduced pH on foraging performance of Nassarius festivus is studied. N. festivus becomes more inactive and reduces its respiration rate at pH 7.0. Travel speed, percentage foraging success and consumption rate worsen at pH 7.0. Respiration rate and foraging performance return to normal upon recovery at pH 8.0. Results imply that acidification impairs the chemosensory functions of N. festivus.